Seven-year monitoring of mercury in wet precipitation and atmosphere at the Amsterdam Island GMOS station. Issue 3 (March 2023) - Tassone, Antonella; Magand, Olivier; Naccarato, Attilio; Martino, Maria; Amico, Domenico; Sprovieri, Francesca; Leuridan, Hippolyte; Bertrand, Yann; Ramonet, Michel; Pirrone, Nicola; Dommergue, Aurelien
Abstract: Mercury (Hg) fate and transport research requires more effort to obtain a deep knowledge of its biogeochemical cycle, particularly in the Southern Hemisphere and Tropics that are still missing of distributed monitoring sites. Continuous monitoring of atmospheric Hg concentrations and trend worldwide is relevant for the effectiveness evaluation of the Minamata Convention on Mercury (MCM) actions. In this context, Gaseous Elemental Mercury (GEM) and total mercury (THg) in precipitations were monitored from 2013 to 2019 at the Amsterdam Island Observatory (AMS - 37°48′S, 77°34′E) to provide insights into the Hg pathway in the remote southern Indian Ocean, also considering ancillary dataset of Rn-222, CO2, CO, and CH4 . GEM average concentration was 1.06 ± 0.07 ng m −3, with a slight increase during the austral winter due to both higher wind speed over the surface ocean and contributions from southern Africa. In wet depositions, THg average concentration was 2.39 ± 1.17 ng L −1, whereas the annual flux averaged 2.04 ± 0.80 μg m −2 year −1 . In general, both GEM and Volume-Weighted Mean Concentration (VWMC) of THg did not show an increasing/decreasing trend over the seven-year period, suggesting a substantial lack of evolution about emission of Hg reaching AMS. Air masses Cluster Analysis and Potential Source Contribution Function showed that oceanic evasion was the main Hg contributor at AMS, while further contributions were attributable to long-range transport events from southern Africa, particularly when the occurrence of El Niño increased the frequency of wildfires. Graphical abstract: Image 1 Highlights: Gaseous Elemental Mercury at Amsterdam Island varied between 0.70 and 1.58 ng m −3 Total mercury concentration in wet deposition ranged from 1.16 to 4.67 ng L −1 CO, CO2, and CH4 concentrations showed upward significant trends from 2013 to 2019. Gaseous Elemental Mercury was affected by El Niño-modulated biomass burning. Atmospheric mercury was governed by oceanic evasion and long-range transport.